Recentring Africa: from Paulin Hountondji to Meinrad Hebga - KITI, PAUL CHRISTIAN (My University, 2018)
The encounter with the Western world has socially, politically, religiously, technologically, economically and intellectually weakened the African people. In other words, this encounter led to the relegation of Africa to the periphery of the world. Here arise the main questions at the background of this reflection: how can we today recentre Africa? To what extent can we say that the thoughts of Paulin Hountondji and Meinrad Hebga shed some lights on our attempt to recentre Africa and refocus research on African endogenous knowledge today?
Keywords: Recentre; Africa; logic of extroversion; rationality; endogenous knowledge; research